Data Sheet 1_The DIAMONDS intervention for type 2 diabetes for people with severe mental illness: findings from a single-group feasibility study.pdf - J. V. E. Brown (13116521) (2025)
Diabetes self-management is critical for improving health outcomes, but people with severe mental illness (SMI) face additional barriers that complicate effective engagement with self-management behaviours and with existing diabetes services. This feasibility study assessed the acceptability and feasibility of the DIAMONDS intervention, a tailored type 2 diabetes (T2D) self-management programme designed for people with SMI and delivered by trained coaches over 16 weekly sessions, in preparation for a future randomised controlled trial (RCT). Thirty participants with both T2D and SMI were recruited, and 29 were included in the study. The thresholds for participant recruitment and retention for progression to the RCT were met. Twenty-three participants (66%) attended at least one intervention session. Consistent weekly participation proved challenging, with only 15 participants (52%) attending eight or more (50%+) sessions. However, the intervention was acceptable to both participants and coaches, as indicated by coach session logs. High completion rates were observed for self-reported measures, while physical health data and data from primary care records had some omissions, prompting refinements in data collection for the RCT. This study highlights the feasibility and acceptability of delivering an evaluation of a structured diabetes self-management intervention in people with SMI. Some modifications to study processes will be required before moving to the main RCT, including adjustments to intervention delivery (including more flexibility in the timing of intervention sessions and coach training to improve confidence in supporting the use of a mobile app), data collection processes, and intervention fidelity assessment for the RCT, to enhance adherence and accommodating the complex needs of this population. This study represents an important step towards the development and robust evaluation of a self-management intervention to improve diabetes outcomes for people with SMI, addressing a significant gap in health equity. Clinical Trial Registration https://www.isrctn.com/ISRCTN15328700, ISRCTN 15328700.